Effectiveness of Digital Literacy Interventions on the Adoption of the Jaminan Kesehatan Nasional, Mobile Application: The Technology Acceptance Model Approach - Hartati Inaku; Nur Uyuun I. Biahimo (Publik : (Jurnal Ilmu Administrasi), 2025)
Digital transformation in public healthcare requires more than the mere provision of technology; successful adoption is fundamentally shaped by users' perceptions and behavioral intentions toward digital applications. In the Indonesian context, the utilization of the Mobile JKN (mJKN) application remains suboptimal, particularly among non-clinical participants of the National Health Insurance (JKN) program. This study therefore, aims to examine the effectiveness of a digital literacy education intervention in enhancing perceived ease of use (PEOU), perceived usefulness (PU), and intention to use the mJKN application, drawing upon the Technology Acceptance Model (TAM) framework. Employing a quasi-experimental one-group pretest–posttest design, the study involved 115 JKN participants in Gorontalo City. Data were collected using a TAM-based instrument and analyzed through paired sample t-tests to assess changes in mean scores before and after the intervention. The findings reveal statistically significant improvements across all three constructs, with PEOU increasing from 3.00 to 3.23, PU from 3.16 to 3.32, and intention to use from 3.12 to 3.26. In addition, user engagement with application features improved, particularly for the online queue function (43.47%) and participant information (26.95%), although a substantial proportion of respondents (46.08%) had not yet explored other available features. These results indicate that community-based digital literacy interventions play a critical role in reshaping user perceptions and fostering stronger intentions to adopt public service technologies. Consequently, the study not only reinforces the applicability of TAM within grassroots contexts in Indonesia but also highlights the importance of user-centered application design that is responsive to local needs in advancing sustainable digital health service adoption.